Evaluating the role of alcohol consumption in breast and ovarian cancer susceptibility using population‐based cohort studies and two‐sample Mendelian randomization analyses. Issue 6 (13th October 2020) - Ong, Jue‐Sheng; Derks, Eske M.; Eriksson, Mikael; An, Jiyuan; Hwang, Liang‐Dar; Easton, Douglas F.; Pharoah, Paul P.; Berchuck, Andrew; Kelemen, Linda E.; Matsuo, Keitaro; Chenevix‐Trench, Georgia; Hall, Per; et al.
Abstract: Alcohol consumption is correlated positively with risk for breast cancer in observational studies, but observational studies are subject to reverse causation and confounding. The association with epithelial ovarian cancer (EOC) is unclear. We performed both observational Cox regression and two‐sample Mendelian randomization (MR) analyses using data from various European cohort studies (observational) and publicly available cancer consortia (MR). These estimates were compared to World Cancer Research Fund (WCRF) findings. In our observational analyses, the multivariable‐adjusted hazard ratios (HR) for a one standard drink/day increase was 1.06 (95% confidence interval [CI]; 1.04, 1.08) for breast cancer and 1.00 (0.92, 1.08) for EOC, both of which were consistent with previous WCRF findings. MR ORs per genetically predicted one standard drink/day increase estimated via 34 SNPs using MR‐PRESSO were 1.00 (0.93, 1.08) for breast cancer and 0.95 (0.85, 1.06) for EOC. Stratification by EOC subtype or estrogen receptor status in breast cancers made no meaningful difference to the results. For breast cancer, the CIs for the genetically derived estimates include the point‐estimate from observational studies so are not inconsistent with a small increase in risk. Our data provide additional evidence that alcohol intake is unlikely to have anything other than a very small effect on risk of EOC. What's new?: While observational studies indicate that alcohol intake is a probable cause of breast cancer, confounding is problematic. For ovarian cancer, meanwhile, evidence linking risk to alcohol consumption remains inconclusive. Here, the authors examined links between alcohol intake and breast and ovarian cancer using observational data from population‐based cohorts combined with Mendelian randomization analyses on large cancer consortia. Observational data identify an association between elevated alcohol consumption and increased susceptibility to breast cancer but not ovarian cancer. Inclusion of genetically derived estimates, however, indicates that alcohol consumption is unlikely to be a major risk factor for breast or ovarian cancer.